THE EFFECT OF METACOGNITIVE STRATEGY ON STUDENTS GRAMMAR MASTERY AT MADRASAH ALWASLIYAH YPP RIDHO ALLAH KAMPUNG PERLABIAN - Octa, Mentari (BRIGHT VISION Journal of Language and Education, 2021)
The purpose of this study was to determine the significant effect of metacognitive strategies on grammar mastery of class XI students, especially in if conditional sentences . Type of research is using the method of research quantitative with the design of experiments . Researchers took data from the MADRASAH ALIYAH YPP RIDHO ALLAH, KAMPUNG PERLABIAN. The population in class XI is 40 students , and there are 2 classes . Each class has 20 students . The entire amount of the population of the sample in the study of this . In this study, there were 2 classes, namely the experimental class (XI-A) and the control class (XI-B) . Researchers gave a pretest before applying treatment and posttest after treatment. Then the researchers analyzed the data of the use of the formula statistic and Microsoft Excel with a level of significance 0 , 05 . Then the researcher gets the data from the study , namely The result is t count (8.55)> t table (1.69) which means that Ha is accepted while Ho is rejected. These results were obtained from the pretest and posttest scores of the students from the experimental class and the control class, where the posttest scores in the experimental class were higher than the control class . Can be concluded that Ha is accepted which is contained the influence of metacognitive strategies that significantly towards mastery of grammar studentsKeyword: metacognitive, grammar if conditional